Relationship between superior-subordinate relationships quality and group commitment: the mediating factor of superior-subordinate communication - Hassan Abu Bakar; Che Su Mustaffa (Universiti Kebangsaan Malaysian, 2008)
Existing researches in explaining superior-subordinates communication are insightful, but give little consideration to the extensiveness of communication activities that can influence various activities in organization. This study proposes and examines superior-subordinate communication as mediating variable. Statistical analysis procedures for testing mediating variable proposed by Baron and Kenny (1986) were used in this study. Our analysis based on this procedure shows superior-subordinate communication acts as a full mediation variable in affecting relationship between superior-subordinate communication acts as a full mediation variable in affecting relationship between superior-subordinate relationships quality and group commitment.